Selection of Recipient Vessel in Traumatic Lower Extremity - Yazar, Sukru; Lin, Chih-Hung (Journal of Reconstructive Microsurgery, 2012)
The main focus of this paper is the selection of proper vessels for successful free tissue transfer in lower extremities which have suffered extensive trauma. The selection of proper recipient vessels for traumatized lower extremities still presents difficulties for surgeons. This review will provide a general guideline for the selection of proper recipient vessels in traumatic lower extremity reconstruction and describe the possible reasons why some recipient vessels present more problems than others.
Keywords: recipient vessel; free flap; lower extremity reconstruction